Virtual Kedah e-Tour / Azyani Ab. Aziz - Azyani, Ab. Aziz (2003)
Virtual Kedah e-Tour system is a tourism system which has a concept of multimedia in presenting the information in the sense of virtual in the website The system is in English version.The selected destination is Kedah This system is consist of 6 main module which are General Info, Paddy Field, Langkawi, Photo Tour, Hotels and Contact Us. Virtual Kedah E-tour system is built for exploiting the unique and speciality of destination for the tourist through the balance multimedia particles. This system generates the virtual scene so that the tourist will feel the real destination before they go to the destination. Besides, this system is also built globally to promote the tourist information. in spite, building this system will reduce the expenses of sending information and to avoid operating information manually. In building Virtual Kedah e-Tour system the software that been used is Maccromedia Flash, Macromedia Dreamweaver MX, Adobe Photoshop and others.